TEACHERS' PERCEPTIONS IN IMPLEMENTING A GENRE-BASED APPROACH TO ENCOURAGE DEEP LEARNING - Salsabilah, Putri; Muljanto, Setia; Nur Fajriah, Yustika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of the Genre-Based Approach (GBA) in fostering deep learning within the Merdeka Curriculum, a crucial topic because although the GBA is formally recommended, many teachers still face challenges in effectively applying it to achieve depth of understanding in the classroom. This study aims to explore teachers’ perceptions and challenges regarding the integration of these two concepts through a qualitative case study design, in which data were collected via semi-structured interviews and observations of two English teachers at the junior high and senior high school levels in Garut. The findings reveal that teachers hold positive perceptions and view GBA as a systematic framework capable of supporting students’ deep understanding through a learning process that is meaningful, mindful, and joyful. Teachers believe that the GBA cycle stages are highly effective in helping students master the material progressively. However, the main challenges identified relate to time management and the diversity of students’ abilities, which hinder the implementation of all GBA stages in their entirety within a single class session. In conclusion, GBA holds great potential for supporting deep learning, but its effectiveness is highly dependent on practical classroom conditions and on-the-ground implementation support.